Pengaruh Pemberian Media Computer Assited Intruction (CAI) untuk Meningkatkan Pemahaman Siswa Terhadap Materi Ajar Pencegahan, Penanggulangan Narkoba dan Psikotropika pada Siswa Kelas VIII SMP Negeri 1 Sawahan Nganjuk - Aditya Sutanegara (Universitas Nusantara PGRI Kediri, 2023)
The purpose of this study was to find out: (1) Know the effect of computer assisted instruction (CAI) on student understanding (2) Know the effect of the lecture method on student understanding. (3) knowing the differences in the interactions between the differences in the interactions between students' mastery of understanding. This research is using experimental method. The population in this study is the population used in this research plan are all students of class VIII SMP Negeri 1 Nganjuk, a total of 8 classes with a total of 244 students. The sampling technique used is random, namely randomly by drawing lots. From a sample of 80 people, the CAI learning model and the lecture method were applied, where the results were classified into two, namely high understanding results and low understanding results. Data collection techniques with test questions and to measure student interest used a questionnaire. The data analysis technique used is ANOVA 2 X 2 and the Newman Keuls test. The results of the study: 1) The results of the study show that there is an effect of learning with CAI media to have a different increase between male and female students. This is evidenced by the value of 89.5> 70.75 at a significance level of 5%. 2) From the results of the study, it was shown that there was an effect of the lecture method treatment having an increase in different learning outcomes between male and female students who received lecture method learning. This is evidenced by the daughter's score of 74.5 > 60.2 and 3) The results of the study show that there is an interaction between the differences in CAI media learning and the lecture method learning model. Because CAI learning media > lecture method learning model thus the null hypothesis (Ho) is rejected which means that the success of the learning approach is influenced by CAI learning media for students. The conclusions of this study are (1) There is a significant effect of giving CAI media on increasing the understanding of class VIII students of SMPN 1 Sawahan. (2) There is the effect of giving